Increased Daytime Sleepiness in Patients with Childhood Craniopharyngioma and Hypothalamic Tumor Involvement: Review of the Literature and Perspectives - Hermann L. Müller (International Journal of Endocrinology)
Childhood craniopharyngiomas are rare embryogenic malformations of the sellar region, presumably derived from Rathke cleft epithelium. The overall survival rates after neurosurgical intervention and/or irradiation are high (92%). However, the quality of survival is frequently impaired due to endocrine deficiencies, sleep disturbances, daytime sleepiness, and severe obesity caused by hypothalamic lesions. Based on self-assessment using nutritional diaries, caloric intake was similar in patients and BMI-matched controls. Analyses of physical activity by accelerometric measurements showed a markedly lower level of physical activity. Significant daytime sleepiness and disturbances of circadian rhythms have been demonstrated in obese childhood craniopharyngioma patients. Daytime sleepiness and obesity in these patients were both correlated with low nocturnal and early morning melatonin levels. Polysomnographic studies in patients with severe daytime sleepiness revealed sleeping patterns typical for secondary narcolepsy. Reports on a beneficial effect of treatment with central stimulating agents supported the hypothesis that secondary narcolepsy should be considered as a rare cause for severe daytime sleepiness in patients with childhood craniopharyngioma.